Posterior shoulder instability: a systematic review. Issue 1 (18th May 2020) - Longo, Umile Giuseppe; Ciuffreda, Mauro; Locher, Joel; Casciaro, Carlo; Mannering, Nicholas; Maffulli, Nicola; Denaro, Vincenzo
Abstract: Introduction: This review aims to provide information on outcomes of surgical procedures for soft tissue or bony glenoid and/or humeral abnormalities in case of posterior shoulder instability. Source of data: A systematic review of the literature according to the PRISMA guidelines was performed. A comprehensive search of PubMed, Medline, CINAHL, Cochrane, Embase, Ovid and Google Scholar databases using various combinations of the keywords 'shoulder', 'posterior instability', 'dislocation', 'reversed bony bankart', 'reversed Hill Sachs', and 'capsulolabral' was performed. Areas of agreement: A total of 847 shoulders in 810 patients were included. A redislocation event occurred in 33 (8.7%) of 411 shoulders with soft tissue abnormalities and in 12 (9.1%) of 132 shoulders with bony abnormalities of the glenoid, humeral head or both. Areas of controversy: The optimal treatment modalities for posterior shoulder dislocation remain to be defined. Growing points: Operative stabilization for posterior shoulder instability should be lesion-specific and should correct all components of the posterior instability. Areas timely for developing research: Future prospective studies should aim to establish the optimal treatment modalities for posterior shoulder instability.